2021
DOI: 10.3889/oamjms.2021.5846
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Acute Kidney Injury in COVID-19 Patients: A Systematic Review

Abstract: BACKGROUND: Acute kidney injury (AKI) in coronavirus disease-19 (COVID-19) has high incidence and mortality. Risk factors for AKI in COVID-19 patients are not well explored. This systematic review provides a combination of available evidence regarding risk factors of AKI in COVID-19 patients. METHODS: A systematic research was performed in Medline, Cochrane Central Register of Controlled Trials, and ScienceDirect journal databases from 2019 to August 2020. The study selection process was plotted using a Prefer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
1
3
0
1
Order By: Relevance
“…Looking at the inflammatory markers, univariable analysis found that LDH ( p < 0.001), hsCRP ( p = 0.001), and AST( p = 0.001) increased the odds of in-hospital mortality, while albumin decreased it ( p = 0.011). These results were comparable to the meta-analyses of Cai et al (2021) [ 10 ] and Daniella et al (2021) [ 11 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Looking at the inflammatory markers, univariable analysis found that LDH ( p < 0.001), hsCRP ( p = 0.001), and AST( p = 0.001) increased the odds of in-hospital mortality, while albumin decreased it ( p = 0.011). These results were comparable to the meta-analyses of Cai et al (2021) [ 10 ] and Daniella et al (2021) [ 11 ].…”
Section: Discussionsupporting
confidence: 90%
“…This study emphasized the high incidence of AKI in a CKD population (77%), compared to patients with undiagnosed CKD but with low baseline eGFR (39%) and those with normal eGFR (8%). The meta-analyses of Cai et al (2021) [ 10 ] and Daniella et al (2021) [ 11 ] both showed that underlying CKD was strongly associated with AKI. Damage to viable nephrons leads to a reduction in renal functional reserve, predisposing to AKI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is pertinent to mention that the reviews reporting the lowest (23,26,39) and highest (28, 35,42,45,46) incidence of CAKI did not explain the reasons for such variations. However, the disease severity was reported as the most common contributor to the variable incidence of CAKI among COVID-19 patients.…”
Section: Discussionmentioning
confidence: 90%
“…Dalam studi yang dilakukan oleh Daniella (2021) ditemukan bahwa tiap peningkatan 1% kadar HbA1C akan meningkatkan risiko mengalami neuropati diabetik sebesar 2.8 kali lipat. Semakin lama seseorang menderita DM, proses tersebut akan berlangsung lebih lama dan pada akhirnya semakin merusak sel saraf (15). Hal tersebut dibuktikan dalam penelitian Lee (2015) yang menemukan bahwa prevalensi neuropathy diabetik pada pasien dengan DM < 5 tahun sebesar 20,8% dan pada DM >10 tahun sebesar 36,8% (16).…”
Section: Pembahasanunclassified